2023
DOI: 10.3390/foods12102018
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for the Development and Optimization of Gluten-Free Noodles Using Flours from Byproducts of Cold-Pressed Okra and Pumpkin Seeds

Abstract: The significant protein and dietary fiber content of cold-pressed pumpkin (PSF) and okra (OSF) seed byproducts are well-known. However, their impact on noodles’ nutritional quality has never been studied. For the first time, noodle formulation was developed employing a genetic algorithm in the R programming language to achieve the most optimal sensory attributes as well as nutritional composition, color, cooking, and textural properties. The optimized noodle formulation was detected for OSF, PSF, gluten-free f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
3
2
0
Order By: Relevance
“…Pumpkin cake flour was found to contain 9.14% ash [19], while another study found 6.86% ash content in pumpkin peel flour [10]; both studies revealed a high percentage of ash in pumpkin cake flour and pumpkin peel flour compared to the 4.01% ash content of PSF in this study. This result corroborates that obtained by Aydin et al [20], who reported a result of 3.55% ash in PSF.…”
Section: Physical-chemical Analysis and Proximal Compositionsupporting
confidence: 93%
“…Pumpkin cake flour was found to contain 9.14% ash [19], while another study found 6.86% ash content in pumpkin peel flour [10]; both studies revealed a high percentage of ash in pumpkin cake flour and pumpkin peel flour compared to the 4.01% ash content of PSF in this study. This result corroborates that obtained by Aydin et al [20], who reported a result of 3.55% ash in PSF.…”
Section: Physical-chemical Analysis and Proximal Compositionsupporting
confidence: 93%
“…The moisture and residual lipid contents of CPC were 4.65 g/100 g and 12.76 g/100 g, respectively (Table 2). These values coincide with those obtained in [9], while [25,26] reported higher values for residual lipids, 16.68 and 14.23 g/100 g, respectively. Data in the literature on the protein content of press cake from pumpkin seed oil production vary between 38.3 and 62.3% [9,[25][26][27].…”
Section: Physicochemical Analysis Of Cpcsupporting
confidence: 89%
“…These values coincide with those obtained in [9], while [25,26] reported higher values for residual lipids, 16.68 and 14.23 g/100 g, respectively. Data in the literature on the protein content of press cake from pumpkin seed oil production vary between 38.3 and 62.3% [9,[25][26][27]. These differences are most likely due to the species and variety diversity and the climatic conditions during the cultivation of the plant raw material.…”
Section: Physicochemical Analysis Of Cpcsupporting
confidence: 89%
“…The development of new gluten-free products is growing; in addition to individuals who need to pursue a gluten-free diet, there has been a growing ask for gluten-free products from those aiming to pursue a healthy eating regimen …”
Section: Discussionmentioning
confidence: 99%